Model based predictive control applied to the aircraft longitudinal mode for a terrain following task - Gustavo Lima Carneiro (2009)
In the present work, a study is proposed about the applicability of a predictive controller to be used to control the longitudinal mode of an aircraft. The objective is to evaluate the performance of such control approach applied to a terrain following task, verifying the tracking suitability while respecting physical constraints to which the aircraft is subjected to. As examples, control surfaces range limitations, restrictions for the available thrust as well as other variables such as the angle of attack, velocity, pitch rate and the altitude itself. A fighter aircraft simplified model was used for the longitudinal movement to perform the simulations. The predictive control approach used was based on a linear prediction model described in the state space. Therefore, it was necessary to linearize the aircraft dynamic around an equilibrium point previously chosen. Two scenarios were evaluated for the same terrain profile. The first considered the simulation with the system nominal constraints. The second scenario covered an elevator actuator failure, in order to analyze the suitability of such controller when dealing with the online imposed constraints. The advantages of the predictive control methodology were evident based on the results for both scenarios, where an adequate terrain profile tracking was observed and, at the same time, the imposed restrictions were enforced in the performed simulations.